1992
DOI: 10.1105/tpc.4.6.631
|View full text |Cite
|
Sign up to set email alerts
|

Normal and Abnormal Development in the Arabidopsis Vegetative Shoot Apex.

Abstract: Vegetative development in the Arabidopsis shoot apex follows both sequential and repetitive steps. Early in development, the young vegetative meristem is flat and has a rectangular shape with bilateral symmetry. The first pair of leaf primordia is radially symmetrical and is initiated on opposite sides of the meristem. As development proceeds, the meristem changes first to a bilaterally symmetrical trapezoid and then to a radially symmetrical dome. Vegetative development from the domed meristem continues as le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(38 citation statements)
references
References 20 publications
1
37
0
Order By: Relevance
“…We examined the cell division planes in the Brachypodium spikelet meristem and found that the outer two cell layers in the meristem apex, L1 and L2, are dominated by anticlinal divisions (Figure S4). This suggests that, similar to wheat and Arabidopsis [42], [43], Brachypodium has a two-layered tunica. Cell divisions in the tunica layers that are parallel to the meristem surface (periclinal) mark the beginning of leaf morphogenesis, and allowed us to easily identify incipient lemma primordia [44] (Figure S4, arrows).…”
Section: Resultsmentioning
confidence: 95%
“…We examined the cell division planes in the Brachypodium spikelet meristem and found that the outer two cell layers in the meristem apex, L1 and L2, are dominated by anticlinal divisions (Figure S4). This suggests that, similar to wheat and Arabidopsis [42], [43], Brachypodium has a two-layered tunica. Cell divisions in the tunica layers that are parallel to the meristem surface (periclinal) mark the beginning of leaf morphogenesis, and allowed us to easily identify incipient lemma primordia [44] (Figure S4, arrows).…”
Section: Resultsmentioning
confidence: 95%
“…The calyx lobes arose first and formed the calyx tube (Figs. The fuf mutation did not cause detectable alteration in meristem zonation nor the shape and differentiation of vegetative organs, but it produced club-shaped siliques (Medford et al, 1992). 26).…”
Section: Vegetative Meristems and Establishment Of Floral Meristems Imentioning
confidence: 99%
“…The subsequent differentiation of floral organs in the fasciation mutants was analogous to normal flower development. formative region (Medford, 1992). 25, 27), and the next whorl formed was the petals whose primordia alternated with the lobes of the calyx (Fig.…”
Section: Vegetative Meristems and Establishment Of Floral Meristems Imentioning
confidence: 99%
See 1 more Smart Citation
“…When injected into a single cell,its movement to neighbouring cells reveals the symplasmic pathways open for the diffusion of small metabolites, hormones and other regulators. Similarly, the Arabidopsis mutants Fey and Dip which early in development loose the ability to maintain a central undifferentiated AM area (Medford et al 1992), might be impaired in the mechanism which closes the plasmodesmata at the field boundaries. 7).…”
Section: Symplasmic Fieldsmentioning
confidence: 99%